Emotions and visual preferences of consumers towards native and classic potato (Solanum tuberosum) chips: Comparative study using neurogastronomy and neuromarketing (Scientia Agropecuaria, 2023)
The use of technological tools, in addition to traditional techniques, to understand consumer emotions and preferences for food products is very important so that product developers have better information for decision-making. This study aimed to use neurogastronomy and neuromarketing tools to study consumers' emotions and visual preferences toward native and classic potato flakes (Solanum tuberosum). Two types of fried flakes were used, classic potato and native potato, with a cost of S/ 6.60 (1.79 USD) and S/ 7.00 (1.90 USD), respectively. Eye Tracking technology and Emotion Analysis were used in the first stage using a mobile phone application. In the second stage, each participant answered a cognitive survey, using the Google form. A hundred consumers aged between 14 and 63 years were used. The survey showed that 45% of consumers indicated their intention to buy the native product rather than the classic product. The neuromarketing results mainly showed a higher proportion of neutrality, and a little lower, in negative emotions of "skepticism", "sadness" and "disgust", especially on the nutritional factor and price. These results, more than contradictory, are complementary since technological tools allow us to know more details about preferences and choices. Consumers intend to consume more native products, if they are more nutritious, more sustainable, cheaper, and benefit the local producer.
Keywords: native potato; strategic decision making; market research; preferences and emotions; neuromarketing